(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article examines the integration of modern technologies into the healthcare system and analyzes the possibilities of personal health monitoring using mobile applications. Mobile applications are considered an important tool in the healthcare sector to ensure effective communication between patients and medical professionals, to assist in health monitoring, diagnosis, and preventive measures. The article highlights the functions of applications designed for health monitoring, including the ability to study heart rate, blood pressure, step counting, and diet control. In addition, the article analyzes the positive and negative effects of technology on health, focusing on issues such as ensuring the privacy of personal data, assessing the scientific validity of applications, and increasing the level of trust in technology among users. The authors highly appreciate the potential of mobile technologies to improve health, presenting them as the future of health care.